2020
DOI: 10.1177/2058738420936386
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the sepsis severity score

Abstract: Introduction: Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. Mortality rates are high, exceeding 50% in patients with septic shock. The sepsis severity score (SSS) was developed to determine the severity of sepsis and as a prognostic model. The aim of this study was to externally validate the SSS model. Methods: Calibration and discrimination of the SSS were retrospectively evaluated using data from a single-center sepsis registry. Results: Data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Of the studies found in this systematic review, only three predictive models had been subjected to external validation: those led by Osborn, 54 Sivayoham, 55 and Granja 56 . The first had four external validation studies, 64‐67 and the others just one (Table 2). 68,69 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies found in this systematic review, only three predictive models had been subjected to external validation: those led by Osborn, 54 Sivayoham, 55 and Granja 56 . The first had four external validation studies, 64‐67 and the others just one (Table 2). 68,69 …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the discrimination of these three models 54‐56 showed that the maximum area under the ROC curve was 0.84, 56 although in all cases this value was above 70%. However, this study had only undergone one external validation process, 68 whereas another study with an area of 0.736 54 had been submitted to various validation studies 64‐67 . The third model had the lowest discrimination (0.712) and just one external validation study, 55,69 although it attained better indicators in PROBAST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the clinical application of DNI, clinical scoring systems such as APACH score, SOFA score and SAPS score have been widely used [ 18 , 19 ]. However, such scoring systems need many parameters such as blood pH, Glasgow coma scale and vital signs to have a final score and take time to draw arterial and venous blood and test electrolytes [ 20 ]. Consequently, those complex processes may be at risk of some complications, such as subcutaneous hematoma and pseudo-aneurysm after blood sampling and time spent of at least 6 h with higher cost.…”
Section: Discussionmentioning
confidence: 99%
“…It is practical for planning the allocation of resources and evaluating the performance of ICU wards. Mortality risk assessment is also used in clinical trials to characterize and compare patient groups, and is also an important part of quality assessment; risk-adjusted mortality is the most commonly used indicator of the quality of ICU care [ 3 ].…”
Section: Introductionmentioning
confidence: 99%